How Obesity Affects Need for Syndesmotic Fixation in Malleolar Ankle Fractures and Ankle Fracture Severity. Issue 4 (22nd October 2020) - Goodloe, Jonathan B.; Caughman, Alexander; Traven, Sophia A.; Slone, Harris; Gross, Christopher E.
Category: Ankle; Trauma Introduction/Purpose: Obesity affects lower extremity fracture care through increased mechanical loading and has subsequently been associated with higher complication rates following surgical management. However, the association between BMI and need for syndesmotic fixation in the setting of malleolar ankle fractures remains to be elucidated. Therefore, the primary objective of this study was to determine the risk of increased fracture severity and need for syndesmotic fixation as related to BMI. Methods: A retrospective analysis of the NSQIP database was performed for patients undergoing surgical fixation of isolated, closed ankle fractures. Patients were grouped by fracture pattern (uni-, bi- and trimalleolar ankle fractures with or without syndesmotic injury). Demographic data was collected and compared between groups and logistic regression analyses were used to assess the relationship between BMI and ankle fracture pattern. Risk factors for postoperative complications and prolonged operative time were also compared between groups. Results: A total of 15, 841 patients (mean age 48.9 years) were identified for inclusion. Analyses revealed that BMI had a positive association with the incidence of open reduction and internal fixation of the ankle syndesmosis, but there was no association between BMI and malleolar fracture pattern. Conclusion: This study demonstrates that elevated BMI is associated with an increased need for syndesmotic reduction and fixation in malleolar ankle fractures. However, the data did not find conclusive evidence to suggest that obesity was associated with ankle severity when evaluating malleolar involvement. Further literature is needed to further delineate the relationship between obesity and ankle fracture pattern.